Museu da resistência e liberdade Carcará da luz : o uso da memória na arquitetura como instrumento político para a manutenção da resistência social - Guimaraes, Lucas Nobre (2023)
The present work arises from the intention to collaborate with the pillars of transitional justice concerning the Brazilian dictatorial period through a sociocultural architectural project in the typology of a museum for the documentation of this period. The research has two main starting points: the first is related to the increasing dissemination of ultra right-wing extremist ideas at the end of the 10’s, and the second refers to the use of the social and cultural educational value of the Material Heritage related to the Castello Branco Mausoleum in Fortaleza, Ceará. In this sense, the lack of equipment that addresses the issue of tragic memories alluding to the events in Brazil in the twentieth century associated with the emptying of the symbolism of a monument honoring the first military dictator of the period, corroborates the maintenance of thoughts based on negativism and extremism. To this end, as a form of theoretical contribution, a bibliographic review is made covering themes pertinent to museology and museography, memory, typologies of historical social tragedies, phenomenology, environmental psychology, neuroarchitecture, phantasmagoria, immateriality and heritage. Then, the survey of data from surveys done with the society to analyze the relationship of appropriation of space in the memorial sense of the Mausoleum, the specific analysis of the theme from case studies and the diagnosis of the site contribute as a methodology to be developed to culminate in the centrality that the architecture assumes in this work with the goal of being a socio-cultural and educational vector in the urban mesh, in the city of Fortaleza (CE). The proposed project seeks, therefore, to embrace aspects such as symbolism, sensoriality, education and political debate as a way to avoid the repetition of tragic even